Pulmonary Hemodynamic Correlates and Prognostic Value of the Cardiopulmonary Exercise Score in Patients With Left Heart Failure - Qianqian Chen; Wande Yu; Peipei Cheng; Mengyu Zhang; Wei Li; Dandan Wei; Hang Zhang; Hanjia Gao; Xiaoxia Fu (Cardiology Discovery)
Abstract. Objective:. Pulmonary hypertension secondary to left heart failure is associated with an abnormal response to exercise and poor prognosis. The objective of this study is to develop an algorithm by using data from cardiopulmonary exercise testing (CPET) to assess the severity of pulmonary hemodynamics and predict clinical worsening and mortality in patients with heart failure. Methods:. From April 2017 to December 2018, a total of 102 patients with heart failure who underwent CPET and invasive right heart catheterization participated in this prospective study. All enrolled patients had their clinical characteristics, hemodynamic parameters, and CPET results. Based on the CPET data namely peak oxygen uptake, the minute ventilation/carbon dioxide production slope, resting end-tidal carbon dioxide, oxygen uptake/work rate flattening, exercise oscillatory ventilation, and oxygen uptake efficiency slope, a Heart Failure Cardiopulmonary Exercise (HFCE) score was developed. The total score was then calculated to categorize patients into 3 groups: low score (0–3) (n = 31), intermediate score (4–7) (n = 45), and high score (8–14) (n = 26). Clinical events were defined as all-cause death and rehospitalization for heart failure, which were recorded and tracked for at least 12 months. Pearson’s correlation coefficients were calculated to assess the relationship between the HFCE score and hemodynamic parameters, 6-minute walk distance, and N-terminal-pro hormone brain natriuretic peptide. Cox proportional hazards regression analysis was used to identify independent predictors of clinical events. Survival curves for clinical events were generated using the Kaplan-Meier method and compared among the 3 groups with different HFCE scores with a log-rank test. Results:. The high HFCE score group had a higher prevalence of New York Heart Association class Ⅲ–Ⅳ (high score vs. intermediate score vs. low score: 85% (22/26) vs. 56% (25/45) vs. 45% (14/31), P = 0.008), higher N-terminal-pro hormone brain natriuretic peptide levels (high score vs. intermediate score vs. low score: (3,039 ± 2,171) ng/L vs. (2,039 ± 2,353) ng/L vs. (1,438 ± 947) ng/L, P = 0.035), lower 6-minute walk distance (high score vs. intermediate score vs. low score: (312 ± 79) m vs. (362 ± 84) m vs. (363 ± 76) m, P = 0.042) compared to intermediate score or low score. The high HFCE score correlated well with high levels of pulmonary vascular resistance (r = 0.539, P < 0.01), pulmonary artery wedge pressure (r = 0.292, P < 0.01), and mean pulmonary artery pressure (r = 0.474, P < 0.01), as well as low levels of cardiac output (r = –0.357, P < 0.01). Moreover, 46 patients developed composed clinical events at 12 months. In the multivariate model, the HFCE score was an independent predictor of composed clinical events (hazard ratio = 1.142, 95% confidence interval: 1.041–1.253, P = 0.005). Kaplan-Meier analysis showed a significantly higher probability of composed clinical events in patients with a higher HFCE score (Plog-rank = 0.004). Conclusion:. The HFCE score—obtained through CPET—provides valuable prognostic information by indicating the severity of hemodynamics in patients with pulmonary hypertension secondary to left heart failure. It can likely serve as a reliable predictor for clinical worsening and mortality.